ECONOMIC GROWTH AND STOCK MARKET DEVELOPMENTS: EVIDENCE IN AFRICA - Iddrisu, S.; Abdul-Malik, A. (UDS International Journal of Development, 2018)
Abstract This study examines the interaction between stock market developments and economic growth in a sample of 12 African countries using a panel VAR approach with data from 1979-2013. In order to establish the suitability of the data for the study, Cross-Sectional Dependence (CD) test, Unit root test, and Cointegration test were performed. We then estimated the model and from the residuals generated, the impulse response functions (irf) and the forecast error variance decompositions (fevd) were also estimated. As robustness check, we performed autocorrelation Lagrangian Multiplier test on the residuals generated from the panel VAR model estimation and found a significant correlation of all series within and across panels: a basis to conclude that the findings hold for all sampled countries studied, in line with the CD test results. The study found no evidence of contemporaneous relationship between stock market and economic growth in Africa. In the long run, the study found evidence of bidirectional relationship between economic growth and stock market developments, with economic growth having greater explanatory power (about 2.5%) on stock market developments than the former has on the latter. Finally, the study established a significant bidirectional relationship between inflation on one side and then economic growth and stock market developments on the other side. With these conclusions, we recommend that in order to stimulate economic growth and development, it is important African governments or the economic management teams of African countries are aware of this relationship (i.e economic growth-stock market nexus) for the purpose of forecasting and predicting in their economic planning. Â  Keywords: Stock market, Economic growth, Panel VAR, Impulse Response Functions (irf), Forecast ErrorÂ Variance Decomposition (fevd).